Rare case of spontaneous renal calyx rupture due to vesicoureteral junction stone in a horseshoe kidney - Siham Oukassem; Salma Debbi; Chaima Abourak; Ola Messouad, PhD; Omar EL Aoufir, PhD; Laila Jroundi, PhD; Ali Mohammed Miko; Mamoun Diouri; Ayoub Bouhnib; Ahmed Ibrahimi, PhD (Radiology Case Reports)
A 50-year-old patient with a prior history of chronic smoking presented to the emergency department with diffuse abdominal pain, primarily localized to the right hypochondrium and epigastric region, along with nausea, but without fever, vomiting, or urinary symptoms. Laboratory tests were largely unremarkable except for isolated hematuria and a mildly elevated CRP. Given the atypical clinical presentation, a 3-phase abdominal CT scan (without contrast, portal, and delayed phases) was conducted, revealing a horseshoe kidney with an obstructing 4 mm stone at the right ureteral meatus. This obstruction led to dilation of the right ureter and renal calyces. In the delayed phase, a rupture of the right calyx was observed with contrast extravasation into the perirenal space. The patient was managed with conservative intervention, including the placement of a JJ stent, analgesics, and antibiotics. The obstructing stone was expelled during stent placement, and the patient showed a favorable clinical course thereafter. Spontaneous rupture of the renal calyx in a horseshoe kidney due to ureteral obstruction by a small calculus is a rare but significant event. Prompt diagnosis with CT imaging and conservative management, including stent placement, can lead to positive outcomes in complex anatomical presentations such as horseshoe kidneys.